2017
DOI: 10.1037/cep0000118
|View full text |Cite
|
Sign up to set email alerts
|

Safe or out: Does the location of attention affect judgments at first base in baseball?

Abstract: Titchener's law of prior entry states that attended stimuli are perceived before unattended stimuli. Prior entry effects measured with visual stimuli have been generated with both endogenous and exogenous attentional deployment (e.g., by Shore, Spence, & Klein, 2001). In theory, the endogenous form of prior entry may have implications for baseball umpire judgments. Conventionally, umpires are instructed to first attend to the ball when it is hit into play; however, where they attend at the imperative instant o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…A key distinction, though, is that unlike Shore, Spence, and Klein, Schneider and Bavelier did not affirm that endogenous orienting had occurred in their task. A more recent investigation by Redden, d'Entremont, and Klein (2017) provides some support for Schneider and Bavelier's conclusions that endogenous visuospatial orienting might not elicit prior entry-albeit in a more real-world TOJ scenario, in which observers were required to make Bsafe^or Boutĵ udgments at close first-base baseball plays. Redden et al found no evidence that prior entry affected the proportions of Bsafe^versus Bout^judgments in this real-world context.…”
Section: Evidence For and Against Prior Entry From Endogenous Visuospmentioning
confidence: 87%
See 4 more Smart Citations
“…A key distinction, though, is that unlike Shore, Spence, and Klein, Schneider and Bavelier did not affirm that endogenous orienting had occurred in their task. A more recent investigation by Redden, d'Entremont, and Klein (2017) provides some support for Schneider and Bavelier's conclusions that endogenous visuospatial orienting might not elicit prior entry-albeit in a more real-world TOJ scenario, in which observers were required to make Bsafe^or Boutĵ udgments at close first-base baseball plays. Redden et al found no evidence that prior entry affected the proportions of Bsafe^versus Bout^judgments in this real-world context.…”
Section: Evidence For and Against Prior Entry From Endogenous Visuospmentioning
confidence: 87%
“…In the present experiment, we explored whether endogenous orienting of attention does elicit prior entry, while using the enriched attentional diagnostic from Redden, d'Entremont, and Klein (2017). Again, Shore, Spence, and Klein (2001) showed an effect of prior entry in their endogenous-orienting task.…”
Section: Spatial Contingency and Measuring Endogenous Visuospatial Ormentioning
confidence: 99%
See 3 more Smart Citations